Efficacy and safety of video laryngoscope in indwelling gastric tube in severe coma patients: A protocol for systematic review and meta-analysis. Issue 52 (30th December 2022) - Gao, Mengying; Wang, Guoying; Zhang, Yunjiao; Han, Mei; Niu, Huiping; Li, Wenlin
Abstract : Background: We designed this systematic review and meta-analysis protocol to provide new medical evidence for clinical management by comparing the prognostic outcomes of visual laryngoscopy with those of conventional blinded insertion methods. Methods: We will intend to search English databases including Medicine, Embase, Web of Science, Cochrane Central Register of Controlled Trials, Scopus, and Google Scholar. The Chinese databases, such as Wanfang, China Knowledge Network, and China Biomedical Literature Database will also be searched. The outcome measures include intubation success rate, pain score, intubation-related complications, patient satisfaction, operation time, and cost. The Jadad scale will be used to evaluate the methodological quality of each randomized controlled trial in this meta-analysis. We will use the Methodological Index of Non-Randomized Studies criteria to assess the risk of bias in non-randomized study. An I 2 value greater than 50% indicates the presence of significant heterogeneity. P < .05 in a 2-tailed test is considered statistically significant. Results: It is hypothesized that video laryngoscope will provide better outcomes compared with traditional blind gastric tube insertion. Conclusions: The results of our review will be reported strictly following the PRISMA criteria and the review will add to the existing literature by showing compelling evidence and improved guidance in clinic settings.